(untitled) (DARYAFT, 2022)
Quaid-e- Azam Muhammad Ali Jinnah, the Founder of Pakistan was a great personality in the history of the world. He got a higher degree in Law and started his political career on the platform of Indian National Congress but soon understood that their policies are anti-Muslim. So he joined All India Muslim League. He was a great and honorable political leader who was acknowledged by the representatives of different political groups. Mr. Jinnah was an honest, confident and hardworking political figure. This article deals with Mr. Jinnah and fine arts.